Efficacy and safety of switching to bilastine, an H1-antihistamine, in patients with refractory chronic spontaneous urticaria (H1-SWITCH): a multicenter, open-label, randomized, parallel-group comparative study - Fukunaga, Atsushi; Kakei, Yasumasa; Murakami, Sae; Kan, Yuji; Masuda, Koji; Jinnin, Masatoshi; Washio, Ken; Amano, Hiroo; Nagano, Tohru; Yamamoto, Akihisa; Otsuka, Toshihiro; Takahagi, Shunsuke; et al. (Frontiers in Immunology, 2024)
Background: For treating patients with refractory chronic spontaneous urticaria (CSU) resistant to standard doses of 2 nd generation H1-antihistamines (H1AH) the International and Japanese guidelines recommend increasing H1AH dose. The latter also recommends switching to a different H1AH. This study explored if the efficacy of the standard dose of bilastine 20 mg is non-inferior to that of doubledose of H1AH in patients with refractory CSU.Methods: This phase IV, multicenter, open-label, randomized, parallel-group trial evaluated the efficacy and safety of switching treatment to bilastine compared to treatment with a 2-fold dose of H1AH in patients with CSU refractory to standard dose H1AH. The primary endpoint was the mean total symptom score (TSS) at Day 5-7 after the start of administration.Results: Treatment efficacy and safety were evaluated in 128 patients (bilastine, n=64; 2-fold dose of H1AH, n=64). The mean TSS at Day 5-7 after the start of administration was smaller than the noninferiority margin of 0.8, demonstrating non-inferiority of the bilastine switching group to the double-dose H1AH group (0.17 (95% CI -0.32, 0.67)). No difference in Japanese version of Epworth Sleepiness Scale (JESS), DLQI, and urticaria activity score over 7 consecutive days (UAS7) was observed between the two groups. There were no serious adverse events in either group. H1AH-related adverse events occurred in 5 subjects (8 cases) and 2 subjects (3 cases) in the double-dose H1AH and bilastine groups, respectively.Switching treatment to bilastine demonstrated non-inferiority to a double-dose of H1AH in terms of efficacy in patients with CSU refractory to standard dose H1AH with a favorable safety profile.